How We Can Personalize the Infliximab Use in Ulcerative Patients - Ahmed, Mohammed Hussien; El Shennawy, Eslam Mohamed; Mahros, Aya Mohammed (Journal of Coloproctology, 2025)
We aimed to assess the predictors of response to infliximab treatment in individuals with ulcerative colitis to personalize its use.This study included the initial 100 UC patients who were administered Infliximab. We Excluded individuals under 18 years old, primary non-responders, and those who declined participation or measurement of their IFX trough levels. We evaluated laboratory tests conducted within 3 months of assessing clinical and endoscopic remission for patients who already started infliximab. Laboratory data, including albumin and C-reactive protein (CRP) test results, and PANCA were collected. We observed the patients for any clinical changes or problems while they had Infliximab treatment.mean age was 34.36 ± 15.5. 73 cases were male while 27 were female. 36 were smokers. In Multivariate correlation regression, there were strong significant correlations between good response and PANCA, Pan-ulcerative, CRP, ESR, NAR, and Fecal calprotectin.PANCA, Pan-ulcerative colitis (E3), CRP, ESR, NAR and Fecal calprotectin are good predictors of infliximab response
Keywords: infliximab response; ulcerative colitis; Egypt